Searching for the stellar cycles of low-mass stars using TESS data - Ramsay, Gavin; Hakala, Pasi; Gerry, Doyle J. (EDP Sciences, 2025)
We carried out a search for stellar activity cycles in late low-mass M dwarfs (M0–M6) located in the TESS northern and southern continuous viewing zones using data from sectors 1–61 (Cycle 1 to partway through Cycle 5). We utilised TESS-SPOC data, which initially had a cadence of 30 min and was then reduced to 10 min in Cycle 3. In addition, we required for each star to be observed in at least six sectors in each north and south Cycle: 1950 low-mass stars ultimately met these criteria. Strong evidence was seen in 245 stars for a very stable photometric variation that we assumed to be a signature of the stars’ rotation period. We conducted a similar study for solar-like stars and found that 194 out of 1432 stars had a very stable modulation. We then searched for evidence of a variation in the rotational amplitude. We found 26 low-mass stars that showed evidence of variability in their photometric amplitude and only one solar-like star. Some display a monotonic trend over 3–4 years, whilst others reveal shorter term variations. We determined the predicted cycle durations of these stars using a relationship found in the literature and an estimate of the stars’ Rossby number. Finally, we found a marginally statistically significant correlation between the range in the rotational amplitude modulation and the rotation period.